Simulation Design Of Animal Waste Treatment Installation System Using Water Level Control System - I Nyoman Gunung; I Nengah Ludra Antara; I Nyoman Sutarna; Kadek Agus Mahabojana D. P.; Made Dika Nugraha (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
The simulation design of this animal waste treatment plant is a design that applies the sewage treatment plant system which is made to cope with environmental pollution, especially rivers due to indiscriminate disposal of animal waste. Making this animal waste treatment plant provides information to readers or the public about how to design an animal waste treatment plant system and the performance of the sewage treatment system so that people know how to deal with environmental pollution caused by the livestock themselves. The manufacture of this installation system uses data collection methods from direct farmers and theories obtained from books, journals, and articles related to sewage treatment plant theory, plumbing, electricity, and others. Finally, the data was collected by testing the animal dung waste treatment system where the test data was taken from the pH content of the water used for processing the animal dung waste treatment system. The test results on the sewage treatment plant system concluded that in order to obtain optimal results or water pH content, namely the pH content of 6, it is necessary to deposit animal manure between two to three days, while the maximum processing of this system is the pH content of 6.5. and processing of animal manure, which is on the fourth day to get the maximum pH content.